Stress, depression, and anxiety: psychological complaints across menopausal stages - Ming Jun Kuck; Eef Hogervorst (Frontiers in Psychiatry, 2024)
IntroductionWith the number of menopausal women projected estimated to reach 1.2 billion by 2030 worldwide, it is critically important to understand how menopause may affect women’s emotional well-being and how many women are affected by this. This study aimed to explore (i) the relationship between psychological complaints (depression, anxiety, poor memory) across different menopausal stages and (ii) investigate the correlation between resilience, self-efficacy, and perceived stress levels, with psychological complaints and whether this was associated with menopausal stage and/or age.Methods287 respondents completed the Menopausal Quality of Life (MenQoL), Perceived Stress Scale (PSS-10), Brief Resilience Scale (BRS), and General Self-efficacy (GSE) scales. Parametric and non-parametric analysis were used to analyse how bothered women were by self-reported poor memory and feelings of depression and anxiety, alongside perceived stress, resilience, and self-efficacy between women in different menopausal stages using STRAW criteria. The association between protective factors (self-efficacy and resilience) and psychological complaints was analysed with partial correlation analysis controlling for menopausal stages and/or age.ResultsA significant difference was found between the levels of perceived stress, and how bothered women were by feelings of depression and anxiety between early-perimenopausal and post-menopausal women. However, with the inclusion of age as a covariate, menopausal stage no longer predicted the level of self-reported stress and anxiety in menopausal women. There was also no difference between poor self-reported memory, or of self-efficacy or resilience between women in different menopausal stages. However, self-efficacy and resilience were associated with how bothered women were by feelings of depression and anxiety, and the experience of stress. Stress was the only variable to be associated with poor self-reported memory independent of age and/or menopausal status.DiscussionEarly perimenopausal women experienced the highest level of stress and were more severely bothered by feelings of depression and anxiety, with the poorest overall self-reported psychosocial quality of life. Post-menopausal women, however, reported to have similar experiences as premenopausal women. Age explained the associations between menopausal stage, stress and anxiety, but not between depression and different menopausal stages. Resilience and self-efficacy were associated with psychological complaints independent of menopausal stage and age, suggesting that therapies focusing on increasing resilience and self-efficacy may be beneficial to help target these psychological complaints at any time.